2009
DOI: 10.1364/ao.48.003460
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic effects of metal vapor lasers

Abstract: Some fluctuations in the output power of a copper vapor laser with a 16 mm bore were recorded by varying the excitation frequency from 13 to 33 kHz. The effect arises from the laser tube, which performs both as an optical and an acoustic resonator at the acoustic resonant frequencies. It is shown that a similar effect occurs in other metal vapor and copper halide lasers as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
5
4
0
Order By: Relevance
“…The maximum output power of ~1.6 W is obtained at 3.8 torr of air pressure and 17 kHz of frequency. The noticeable point is the oscillatory behavior of the output power in terms of the frequency, which is in agreement with the previous reports [41] [42]. The effect arises from the laser tube which performs both as an optical and an acoustic resonator at some frequencies.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The maximum output power of ~1.6 W is obtained at 3.8 torr of air pressure and 17 kHz of frequency. The noticeable point is the oscillatory behavior of the output power in terms of the frequency, which is in agreement with the previous reports [41] [42]. The effect arises from the laser tube which performs both as an optical and an acoustic resonator at some frequencies.…”
Section: Resultssupporting
confidence: 91%
“…In fact, the discharge energy extracted by optical and acoustical channels due to radiative and non-radiative decays, respectively. It is shown that the non-radiative deactivation vastly increases, when the excitation frequency is equivalent to the acoustic resonant mode of laser tube [41]. Figure 3 illustrates the behavior of the output power versus the pressure of air buffer gas at some frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…The notable point is that the oscillatory behaviour of the output power in terms of frequency is in agreement with our previous reports (Khorasani et al 2008;Zoghi et al 2009). This effect arises from the laser tube, which performs both as an optical and an acoustic resonator at some frequencies.…”
Section: Resultssupporting
confidence: 91%
“…2008; Zoghi et al. 2009). This effect arises from the laser tube, which performs both as an optical and an acoustic resonator at some frequencies.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the figure, the variation of the output power relative to the frequency has oscillatory behaviour. The minimum represents the output power drop, which is related to the acoustic resonance of the laser tube (Khorasani, Salehinia, Behrouzinia, Sajad, & Parvizian, 2008;Zoghi et al, 2009). The repetition frequency has been changed between 14-29 kHz.…”
Section: Fig 4 Variation Of Pout Versus Pinmentioning
confidence: 99%